2018
DOI: 10.1002/jemt.23075
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ 2D bacterial crystal growth as a function of protein concentration: An atomic force microscopy study

Abstract: The interplay between protein concentration and (observation) time has been investigated for the adsorption and crystal growth of the bacterial SbpA proteins on hydrophobic fluoride‐functionalized SiO 2 surfaces. For this purpose, atomic force microscopy (AFM) has been performed in real‐time for monitoring protein crystal growth at different protein concentrations. Results reveal that (1) crystal formation occurs at concentrations above 0.08 µM and (2) the compliance of the formed cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…14,15 This is the case of SbpA from Lysinibacillus sphaericus CCM2177, which presents a square (p4) lattice symmetry, a system that has quite extensively been characterized in literature so far. [16][17][18] Because of the large number of nanometric pores found along the S-layer structure, it can be hypothesized that the release of the drug from the polymeric matrix can be still conducted although to a lower rate.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This is the case of SbpA from Lysinibacillus sphaericus CCM2177, which presents a square (p4) lattice symmetry, a system that has quite extensively been characterized in literature so far. [16][17][18] Because of the large number of nanometric pores found along the S-layer structure, it can be hypothesized that the release of the drug from the polymeric matrix can be still conducted although to a lower rate.…”
Section: Introductionmentioning
confidence: 99%
“…AFM images revealed that lysine acetylation promoted al arger population of proteins in an open conformation,w hich playedarole in the autoimmune disease antiphospholipids yndrome. [52] Such measurementse nabledt he testing of theoreticalc rystal-growth models. The authors could demonstrate that proteins were incorporated within the lipid bilayer through their hydrophobic domains.…”
Section: Molecules and Polymersmentioning
confidence: 99%
“…Moreno-Cencerrado et al followed the formation of 2D bacterial proteins crystals as a functiono ft ime for different protein concentrations (Figure 4). [52] Such measurementse nabledt he testing of theoreticalc rystal-growth models.…”
Section: Molecules and Polymersmentioning
confidence: 99%
See 2 more Smart Citations